Radiocarbon and wood anatomy as complementary tools for generating tree-ring records in Bolivia - Pacheco-Solana, Arturo; Oelkers, Rose; D’Arrigo, Rosanne; Santos, Guaciara M.; Rodriguez-Caton, Milagros; Tejedor, Ernesto; Ferrero, Eugenia; Fuentes, Alfredo F.; Maldonado, Carla; Andreu-Hayles, Laia (Frontiers in Plant Science, 2023)
Tropical dendrochronology is now emerging in areas where tree-ring dating had previously been considered not possible. In this study, we combine novel wood anatomical microsectioning techniques and radiocarbon analysis together to produce the first tree-ring chronology with annual periodicity for a new tree species, Neltuma alba (commonly known as “algarrobo blanco”) in the tropical Andes of Bolivia. First, we generated a preliminary chronology composed of six trees using traditional dendrochronological methods, i.e. based on matching growth patterns among trees (cross-dating). We then measured the 14C content on nine selected tree rings from two samples and compared them with the Southern Hemisphere atmospheric (SH) 14C curves, covering the period of the bomb 14C peak. We find consistent offsets in dating of 5 and 12 years, respectively, indicating that some tree rings in the sequence were missing. In order to identified the tree-ring boundaries of the unidentified rings we investigated further by analyzing stem wood microsections to examine anatomical characteristics. These sections revealed the presence of very narrow terminal parenchyma boundaries within the sapwood, not visible on a sanded wood sample under a stereomicroscope. Such newly identified tree-ring boundaries were consistent with the offsets shown by the radiocarbon analysis and allowed us to correct the calendar dates of the initial chronology. A second round of radiocarbon analysis over a new batch of rings of the corrected dated samples resulted in perfect matching of the dendrochronological calendar years and the 14C dating which is based on the good agreement between the tree-ring 14C content and the SH 14C curve. The correlation analysis reported that below-average precipitation combined with low temperatures, both before the onset of the growing season, limit radial growth at our study site. Our results reveal a strong legacy effect of climate conditions prior to the actual Neltuma alba growing season. Overall, our study highlights the potential to complement dendrochronology in tree species with challenging ring boundaries with wood anatomical methods and 14C analyses, methodological approaches which confirmed here that Neltuma alba can be accurately dated and thereby used in climatic and ecological studies in tropical and subtropical South America.